Analysis of Factors Related to Increased Interdyalitic Weight Gain (IDWG) in Patients with Chronic Kidney Diseases (CKD) in Hemodialysis Unit - Fermata Sari; Lindesi Yanti; Aris Teguh Hidayat; Masniati Arafah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Weight gain between dialysis times (Intradialytic Weight Gain (IDWG)). IDWG values > 6% of dry body weight can cause various complications. Increased IDWG is influenced by various factors both internal and external. It is important to know the factors that influence IDWG in increasing patient compliance with fluid intake. Objective to determine the factors that influence the increase in IDWG of Chronic Kidney Disease Patients in the Hemodialysis Unit Method: The design of this study is descriptive correlation analysis with a Cross Sectional design. The sample of this study was CKD patients with hemodialysis at Dr. AK Gani Hospital, Palembang, the sample was determined through a total sampling technique, totaling 41 respondents. The research instruments consist of demographic data instruments, namely age, gender, education and marital status, fluid intake questionnaires, stress, thirst using standard questionnaires, family support questionnaires have been tested for validity with r results> r table (0.361), and reliable with r Alpha value of 0.749, self-efficacy questionnaires have been tested for validity with r results> r table (0.361), and declared reliable with r Alpha 0.822, and Body Weight is measured using ISO weight scalesAnalysis to determine the relationship between IDWG and fluid intake, thirst, self-efficacy, stress, family support with the Spearman Sign Rank Rho correlation test. There is a significant relationship between IDWG values and fluid intake (p = 0.001 r = 0.603), there is a relationship between IDWG values and thirst (p = 0.001 r = 0.484). There is no relationship between IDWG values and self-efficacy (p = 0.186 r = 0.244). The relationship between IDWG values and stress showed no relationship (p = 0.206 r = 0.202). The relationship between IDWG values and family support had no relationship with IDWG values (p = 0.976 r = 0.005). The increase in IDWG values is influenced by fluid intake and thirst in hemodialysis patients, the higher the fluid intake and thirst, the greater the increase in IDWG values.